ANTAM COMPANY FINANCIAL REPORT IN INDONESIA - Milko Hutabarat; Rudy Sondang Sinaga (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to examine how Indonesian manufacturing companies' financial statements are affected by the implementation of Financial Accounting Standards. The use of SAKs is essential to ensuring that the financial statements provided are pertinent, trustworthy, and comparable in light of the growing complexity of business and the increasing demands for accountability and transparency. Using a quantitative methodology, this study gathers information from the 2021–2023 financial statements of eight industrial businesses listed on the Indonesia Stock Exchange. Multiple regression analysis is the analytical technique employed to examine the link between the quality of financial statements as assessed by indicators of relevance, reliability, comparability, and understandability, and the application of SAK. The study's findings offer empirical support for the notion that applying SAK can enhance the quality of financial statements. They also offer suggestions for policymakers, accountants, and scholars.